Controls on Morphology and Growth History of Coral Reefs of Australia's Western Margin - Collins, Lindsay (Society for Sedimentary Geology (SEPM), 2010)
The western margin of Australia provides a regional latitudinal and climatic gradient from the macrotidal tropical north to the microtidal temperate south, modulated by the poleward-flowing warm Leeuwin Current. Coral-reef systems, discontinuously developed during the late Tertiary–Quaternary, vary from fringing reefs to isolated reefs which rise from deep-ramp settings. Quaternary evolution of the reef systems is being documented using regional mapping, seismic imaging, coring and U-series dating. The well-constrained sea-level data from the Houtman Abrolhos carbonate platforms (at 28–298 S) have also been applied to the less known North West Shelf reefs. The Ningaloo fringing reef at 20–228 S records Holocene and last-interglacial phases of reef growth in a tectonically stable environment. It overlies Tertiary carbonates of the Cape Range, which is flanked by uplifted Plio-Pleistocene terraces and reefs. Scott Reef (at 148 S) is a macrotidal, isolated reef which overlies a carbonate platform and a major gas discovery.Seismic profiles reveal a last-interglacial (ca. 125,000 year) reef system, but reefs which apparently grew to sea-level are 30 m below present sea-level, indicating significant subsidence in the late Quaternary. Contemporary reefs grew during the Holocene in the accommodation space provided by subsidence and are up to 35 m thick. The Rowley Shoals (15–178 S) comprise one of the most perfect morphological series of reefs known, and these emergent, annular reefs rise from depths of 200–400 m. Seismic profiles suggest that late Quaternary subsidence has been an important control on reef growth, while differential subsidence has influenced reef morpho1ogy. Differential geomorphic and physical process settings, seismic stratigraphy, sealevel history, and subsidence are keys to patterns of reef growth which can be seen as responses to these controls.